2022
DOI: 10.1016/j.ijscr.2021.106681
|View full text |Cite
|
Sign up to set email alerts
|

Solitary pulmonary nodule as the initial manifestation of isolated metastasis from prostate cancer without bone involvement: A case report

Abstract: Introduction Isolated lung metastases from prostate cancer without any other organ involvement are rare. They are commonly in the form of diffuse or multiple lesions and rarely emerge as a solitary pulmonary nodule. Presentation of case A 61-year-old man who had undergone a laparoscopic-assisted radical prostatectomy for prostate cancer 16 months prior presented with a growing solitary pulmonary nodule. Positron emission tomography/computed tomography showed an abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…It is actually unclear if the incidence of isolated prostate cancer metastasis to the lung is currently on the rise as we also noticed that in the past year, two similar cases were reported by Yoshitake et al and Kosaka et al [ 12 , 13 ]. However, the cases reported by Yoshitake et al and Kosaka et al showed that pulmonary metastasis was identified in their patients seven years and 1.5 years, respectively, after completing treatment for primary prostate cancer.…”
Section: Discussionmentioning
confidence: 63%
“…It is actually unclear if the incidence of isolated prostate cancer metastasis to the lung is currently on the rise as we also noticed that in the past year, two similar cases were reported by Yoshitake et al and Kosaka et al [ 12 , 13 ]. However, the cases reported by Yoshitake et al and Kosaka et al showed that pulmonary metastasis was identified in their patients seven years and 1.5 years, respectively, after completing treatment for primary prostate cancer.…”
Section: Discussionmentioning
confidence: 63%
“…PCa lung metastasis may manifest with symptoms that primarily result from the spread of cancer cells to the lungs. In the early stages, individuals may not experience noticeable symptoms, and the metastasis may be asymptomatic [13][14][15]. However, as the disease progresses and the metastatic lesions affect lung function and adjacent structures, various symptoms may emerge.…”
Section: Clinical and Laboratoriesmentioning
confidence: 99%
“…PCa cells in lung metastasis often retain the glandular features seen in the primary tumor, aiding in their identification. The majority of lung metastasis in prostate cancer arise from prostate adenocarcinoma, given its status as the most prevalent histological subtype of PCa [14,15,49,50]. Nevertheless, less common histological subtypes, such as small cell carcinoma and neuroendocrine carcinoma of the prostate, have been documented [51][52][53][54].…”
Section: Histopathologymentioning
confidence: 99%
See 2 more Smart Citations